2007
DOI: 10.1007/s00268-007-9197-x
|View full text |Cite
|
Sign up to set email alerts
|

Liver Volumetry Plug and Play: Do It Yourself with ImageJ

Abstract: Background A small remnant liver volume is an important risk factor for posthepatectomy liver failure and can be predicted accurately by computed tomography (CT) volumetry using radiologic image analysis software. Unfortunately, this software is expensive and usually requires support by a radiologist. ImageJ is a freely downloadable image analysis software package developed by the National Institute of Health (NIH) and brings liver volumetry to the surgeon's desktop. We aimed to assess the accuracy of ImageJ f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 27 publications
(30 reference statements)
7
81
0
Order By: Relevance
“…Manual outlining of liver borders for preoperative volumetric evaluation of the liver is time-consuming and has been performed in recent years with specific post-processing software such as OsiriX ® or Image J ® . [4][5][6] The present study showed that volumetry of the liver using Terarecon Aquarius iNtuition ® auto-segmentation was three times faster than manual outlining of the liver with OsiriX ® , while maintaining accuracy.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Manual outlining of liver borders for preoperative volumetric evaluation of the liver is time-consuming and has been performed in recent years with specific post-processing software such as OsiriX ® or Image J ® . [4][5][6] The present study showed that volumetry of the liver using Terarecon Aquarius iNtuition ® auto-segmentation was three times faster than manual outlining of the liver with OsiriX ® , while maintaining accuracy.…”
Section: Discussionmentioning
confidence: 57%
“…The future role of post-processing open source software such as Osirix ® is unclear as the time needed for volumetric assessment of the liver by nonradiologists was almost 20 min in our and sometimes more in previous studies. [4][5][6]11,13 To our knowledge, there is no 'liver plugin' available in OsiriX ® or other open source post-processing software that allows for automated liver segmentation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, MRI has become one of the most universal techniques aimed at visualizing detailed internal structures in the body. The use of contrast agents for MRI provides comparable spatial resolution with far better contrast resolution than CT imaging (21,22). Furthermore, the use of both MRI and fluorescent labeling (i.e., bimodal imaging) to track proteins, cells, and angiogenesis was recently reported (23)(24)(25).…”
Section: Significancementioning
confidence: 99%